VO2 max during swimming flume and treadmill test: specific adaptations in over sixty swimmers - Sardella, F.; Pulejo, C.; Caserotti, P. (Biomechanics and Medicine in Swimming VIII, 1999)
Our investigation focused on the functional adaptations of a group of elderly practising only swimming as a regular physical activity, for it is possible to better evaluate the adaptations to a specific activity in elderly rather than in young people who practice more physical activities. Eight Masters swimming athletes with an average age of 63 years underwent a functional evaluation on two ergometers: treadmill and swimming flume, considering the first not specific and the second one specific for the evaluation of this type of athlete. In the elderly the results showed higher values of: respiratory frequency, ventilation, maximum oxygen uptake, heart rate and lactate values for the swimming test as compared to the ones found for the treadmilL This does not seem to agree with the data found in literature where most of the investigations resulted in higher values for treadmill vs. flume, but it must be considered that the examined subjects were all younger. Therefore, swimming seems to be a suitable sport for stimulating the cardia-circulatory and respiratory apparatus but not as good for maintaining an efficient workout for lower limbs, that have to be stimulated with other motor activities.